PENINGKATAN PEMAHAMAN WAKAF BAGI PENGURUS DEWAN KEMAKMURAN MASJID - Huda, Nurul; Muhammad Rofi'i; Gani, Ariel Nian; Maulana, Aya Yahya; Luhur, Irgi Alfariz; Ashilah, Nasywa Athaya (LPPM Universitas Islam 45 Bekasi, 2025)
This community service program aimed to enhance the knowledge and capacity of Mosque Prosperity Council (DKM) administrators regarding cash waqf as a sustainable alternative funding source for mosques. The training was held on June 20, 2025, at Jami’ YARSI Mosque, involving 18 participants representing mosques around YARSI University. The program employed lectures, interactive discussions, and evaluations through pre-test and post-test. The analysis results indicated a significant improvement in participants’ understanding after the training, as evidenced by a Sig. (2-tailed) value of 0.000 < 0.05. Furthermore, participant evaluations showed highly positive responses to the relevance of the material, the competence of the speakers, and the adequacy of the facilities. Based on this success, the program will proceed to the mentoring stage for establishing a cash waqf nazhir institution, including obtaining official licensing from the Indonesian Waqf Board (BWI) and collaborating with Islamic Financial Institutions authorized to receive cash waqf (LKS-PWU). The implementation of this follow-up stage is expected to realize financial independence for mosques and optimize their role as centers of community economic empowerment based on waqf, thereby providing sustainable benefits for the surrounding community.